Infrared and Visible Photodissociation Spectra of Rhodamine Ions at 3 K in the Gas Phase - Jašík, Juraj; Navrátil, Rafael; Němec, Ivan; Roithová, Jana (The journal of physical chemistry. A, 2015)
Helium-tagging predissociation spectroscopy in the visible spectral range (He@VisPD) is shown for Rhodamine 123, Rhodamine 110, and Rhodamine 110's silver salt (silver carboxylate). It is shown that the spectra reflect single-photon absorption. The helium-tagged ions are in the ground vibrational state, and the He@VisPD spectra feature the Franck-Condon envelopes for the excitation to the first excited singlet state that agree very well with theoretical simulations. The S0 → S1 excitation energies are 2.712 ± 0.006 eV for Rhodamine 123, 2.700 ± 0.006 eV for Rhodamine 110, and 2.751 ± 0.006 eV for the silver salt of Rhodamine 110. The determined energies can be slightly blue-shifted due to the binding energy of helium. The Rhodamine ions were also characterized by helium-tagging infrared photodissociation spectroscopy. The distinctive spectral features of the individual derivatives are described and the spectra are compared to the classical solid-state IR spectra.